2021
DOI: 10.1080/07315724.2020.1869625
|View full text |Cite
|
Sign up to set email alerts
|

A Mediterranean Diet and Low-Fat Vegan Diet to Improve Body Weight and Cardiometabolic Risk Factors: A Randomized, Cross-over Trial

Abstract: Objective: Evidence suggests that both Mediterranean and vegan diets improve body weight and cardiometabolic risk factors, but their relative efficacy has not been compared in a randomized trial. Methods: In a randomized crossover trial, 62 overweight adults were randomly assigned to a Mediterranean or vegan diet for a 16-week period. Body weight, plasma lipids, blood pressure, and body composition (dual X-ray absorptiometry) were measured. Secondary measures included insulin resistance (Homeostasis Model Asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
146
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(150 citation statements)
references
References 41 publications
3
146
0
1
Order By: Relevance
“…There is a lack of a standardized definition of what well-designed vegan and non-vegan diets actually mean in terms of macronutrient composition. The authors of the present paper therefore suggest that well-designed vegan (as used by research that has shown noteworthy results [ 23 , 24 , 25 , 26 ]) and non-vegan diets (as proposed in government guidelines on healthy eating by the Ministry of Health of Slovenia [ 27 ]) should limit total fat intake to up to 20% and 30% of energy, respectively (i.e., saturated fat intake ≤10% of energy for both), fiber intake should be above 60 and 30 g/d, and both diets should limit free sugar intake to ≤5% of energy. The effects of dietary cholesterol on blood lipids remains a matter of debate [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 88%
“…There is a lack of a standardized definition of what well-designed vegan and non-vegan diets actually mean in terms of macronutrient composition. The authors of the present paper therefore suggest that well-designed vegan (as used by research that has shown noteworthy results [ 23 , 24 , 25 , 26 ]) and non-vegan diets (as proposed in government guidelines on healthy eating by the Ministry of Health of Slovenia [ 27 ]) should limit total fat intake to up to 20% and 30% of energy, respectively (i.e., saturated fat intake ≤10% of energy for both), fiber intake should be above 60 and 30 g/d, and both diets should limit free sugar intake to ≤5% of energy. The effects of dietary cholesterol on blood lipids remains a matter of debate [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 88%
“…Dietary intake has been described in detail previously (13). Brie y: Based on the self-reported diet records, energy intake slightly decreased on the vegan diet (p < 0.001) compared with no change on the Mediterranean diet.…”
Section: Dietary Intakementioning
confidence: 96%
“…The methods have been described in detail previously (13). Brie y: This randomized, cross-over trial took place between February and October 2019 in Washington, DC.…”
Section: Study Design and Eligibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The beneficial effect of the MD is probably related to synergistic interactions between the various ingredients as a whole of the nutritional regimen [ 47 ]. A potential mechanism underlying the effect of the MD on the vascular system may be associated with a beneficial impact on endothelium-dependent vasoreactivity and insulin resistance [ 48 , 49 , 50 ], as well as with antioxidant and anti-inflammatory activity [ 51 , 52 , 53 ].…”
Section: Preventive Strategiesmentioning
confidence: 99%